JEMBATAN BETON DENGAN KEPALA JEMBATAN INTEGRAL - Tristanto, Lanneke (Jurnal Jalan Jembatan, 2018)
The use of integral bridge abutments eliminates the need for deck joints and bearings. The absence of joints and bearings significantly reduces construction and maintenance costs, compared to conventional bridge types with joints. A standard design method for integral bridges does not exist. The girders are designed on the safe side, as simple supported girders, that is not taking the restraint from the embankments into account. A short span 22m concrete integral bridge design is being studied for application in future road betterment programs. Integral bridge technology needs still more research for innovation improvement. Satisfactory performance of a full scale execution will increase the integral bridge type selection in future bridge projects.